OHP-013 Assessment of medical devices intended to administer antineoplastic drugs compounded in syringes: methodology proposal. (25th February 2017) - Lefebvre, M; Simon, N; Vasseur, M; Sidikou, O; Barthélémy, C; Décaudin, B; Odou, P
Abstract : Background: The use of a post-administration rinsing process for intravenous antineoplastic drugs is very common to help to control occupational exposure to them. In paediatric haemato-oncology, drugs are often compounded in syringes to reduce the volume to be infused. In this case, extension sets with low deadspace volume are used but the required volume to rinse is not clearly specified. Purpose: The aims of this study were to propose a simple methodology to assess the rinsing volume of syringe extension sets and to compare several marketed devices. Material and methods: A UV spectrophotometry assay using quinine hydrochloride as drug substitute was developed. Quinine concentration ranged from 20 to 200 µg/mL. The assay was validated with the accuracy profile method and tested on 5 different assemblies (device+extension sets) with different deadspace volumes (1.28–2.80 mL) and at two different quinine concentrations (0.3 and 8.0 mg/mL). Rinsing was performed stepwise with water for injection until reaching an undetectable quinine concentration. After fitting the data with a Weibull model, assemblies were compared with an ANOVA performed on ranks (GraphPad, La Jolla, USA). Results: The within day and between day precision ranges were 0.39–0.81% and 0.48–0.84%, respectively. The lower limit of quantification was 4.26 µg/mL. The volume required to completely rinse the infusion line was different according to the initial drug concentration and to the device assessed: from 6 to 10 mL for a low quinine concentration and from 7 to 17 mL for a high quinine concentration. Conclusion: This study shows that a simple, cheap and easy to use methodology may be used to assess the rinsing volume of syringe extension sets. The rinsing volume is different according to the tested device. References and/or acknowledgements: The author thank each supplier who provided free samples for the experiments. No conflict of interest